Inverstigating hard X-ray transients in the Magellanic Clouds - Vasilopoulos, Georgios (XMM-Newton Proposal, 2016)
The Magellanic Clouds harbour a large sample of Be/X-ray binariesat a moderate and well known distance with low Galactic foregroundabsorption. However, the transient nature of Be/X-ray binaries complicatesobservations in X-rays. Serendipitous detections of bright outburstsprovide rare chances for further investigation. We propose three triggeredXMM-Newton observations of new or unexplored systems to continue thebuild up of a large statistical sample of these sources.